Trans‐arterial chemo‐embolization is safe and effective for elderly advanced hepatocellular carcinoma patients: results from an international database. (4th April 2014) - Cohen, Matan J.; Levy, Izhar; Barak, Orly; Bloom, Allan I.; Fernández‐Ruiz, Mario; Di Maio, Massimo; Perrone, Francesco; Poon, Ronnie T.; Shouval, Daniel; Yau, Thomas; Shibolet, Oren
Abstract Objective Hepatocellular carcinoma (HCC) incidence among elderly patients is increasing. Trans‐arterial chemo‐embolization (TACE) prolongs survival in selected HCC patients. The safety and efficacy of TACE in elderly patients has not been extensively studied. The objective of this study was to assess the safety and efficacy of TACE in elderly patients (older than 75) with HCC. Design Combined HCC registries (Spain, Italy, China and Israel) and cohort design analysis of patients who underwent TACE for HCC. Results Five hundred and forty‐eight patients diagnosed and treated between 1988 and 2010 were included in the analysis (China 197, Italy 155, Israel 102 and Spain 94, ). There were 120 patients (22%) older than 75 years and 47 patients (8.6%) older than 80. Median (95% CI) survival estimates were 23 (17–28), 21 (17–26) and 19 (15–23) months (P = 0.14) among patients aged younger than 65, 65–75 and older than 75 respectively. An age above 75 years at diagnosis was not associated with worse prognosis, hazard ratio of 1.05 (95% CI 0.75–1.5), controlling for disease stage, sex, diagnosis year, HBV status and stratifying per database. No differences in complication rates were found between the age groups. Conclusions TACE is safe for patients older than 75 years. Results were similar over different eras and geographical locations. Though selection bias is inherent, the results suggest overall adequate selection of patients, given the similar outcomes among the different age groups.